AUTOREACTIVE ANTIBODIES IN A HEALTHY HUMAN AND IN PATIENTS WITH VIRAL INFECTIONS - V. Z. Krivitskaya (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. This brief review presents the data obtained during the last two decades which allow to create a new view on autoimmunity. Regulatory and protective characteristics of autoreactive natural antibodies and their role in development of effective adaptive antiviral immune response are discussed. The article considers the problem of possible autoimmune complications due to some viral infections and antiviral vaccination.